2018
DOI: 10.1002/jor.24042
|View full text |Cite
|
Sign up to set email alerts
|

Petaloid recombinant peptide enhances in vitro cartilage formation by synovial mesenchymal stem cells

Abstract: In vitro chondrogenesis of mesenchymal stem cells (MSCs) mimics in vivo chondrogenesis of MSCs. However, the size of the cartilage pellets that can be attained in vitro is limited by current methods; therefore, some modifications are required to obtain larger pellets. Petaloid pieces of recombinant peptide (petaloid RCP) have the advantage of creating spaces between cells in culture. The RCP used here is based on the alpha-1 sequence of human collagen type I and contains 12 Arg-Gly-Asp motifs. We examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…(iii) Histological measurements showed significantly higher junctional epithelial height in the β-TCP/RCP group compared to the Ctrl group (Figure 6). On the other hand, RCP promotes proliferation of several types of cells, such as mesenchymal stromal cells, as reported by Muraya et al [38], and synovial mesenchymal cells, as reported by Naritomi et al [39]. In the present study, β-TCP/RCP was found in the gingival fibrous tissue 8 weeks after implantation (Figure 4C), however, these β-TCP/RCP granules were not related to osteogenesis.…”
Section: Discussionsupporting
confidence: 77%
“…(iii) Histological measurements showed significantly higher junctional epithelial height in the β-TCP/RCP group compared to the Ctrl group (Figure 6). On the other hand, RCP promotes proliferation of several types of cells, such as mesenchymal stromal cells, as reported by Muraya et al [38], and synovial mesenchymal cells, as reported by Naritomi et al [39]. In the present study, β-TCP/RCP was found in the gingival fibrous tissue 8 weeks after implantation (Figure 4C), however, these β-TCP/RCP granules were not related to osteogenesis.…”
Section: Discussionsupporting
confidence: 77%
“…Naritomi et al . reported a notable increase in differentiation and an increase in the amount of cartilage matrix produced when MSC CellSaics were used for cartilage differentiation compared to MSCs only [38]. Even in tests performed using a rabbit osteochondral defect model, the results showed accelerated bone cartilage regeneration with the use of MSC CellSaics compared to that shown with MSCs only [39].…”
Section: Application Of Cellsaicmentioning
confidence: 99%
“…To develop new approaches for inducing chondrogenesis of adult stem cells, Naritomi et al showed that petaloid pieces of a recombinant peptide could greatly enhance the chondrogenesis of synovial‐derived MSCs.…”
mentioning
confidence: 99%